Qallunaaliaqtut: Inuit Students’ Experiences of Postsecondary Education in the South - Rodon, Thierry; Lévesque, Francis; Kennedy Dalseg, Sheena (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2015)
The purpose of this study was to learn from the experiences of post-secondary Inuit students from Canada. Through surveys, interviews, and focus groups, we realized that despite the challenges associated with pursuing post-secondary education in the South, most respondents perceived their experience to be positive. Lack of access to sufficient and equitable funding was perceived by respondents to be a significant barrier, as was the lack of readily available information for prospective students from Inuit Nunangat. We conclude with a brief discussion of possible actions for improving access to university education in Inuit Nunangat, notably that governments should not only focus on training and should develop programs that reflect Inuit students’ needs and aspirations.